Public Istanbul Spaces and Spheres of the Urban - Eckardt, Frank; Wildner, Kathrin (Urban Studies, 2008)
Istanbul is one of the largest and most dynamic metropolises on the European continent. In the context of processes of globalization and local urban planning projects urban space is continously contested. In this anthology forms, meanings and images of these urban spaces are discussed by architects, historians, and social scientists. Through interdisciplinary approaches of theory and case studies the book delivers a deep insight into the construction and constitution of public spaces and spheres in contemporary Istanbul.